Monsoon and Tropical Climate Forcing on the Physicochemical and Thermocline Characteristics of the Maldives Inner Sea: Insights From Marine Isotope Stages 1–2 and 10–13. Issue 6 (28th May 2021) - Stainbank, Stephanie; Spezzaferri, Silvia; Rüggeberg, Andres; Raddatz, Jacek; de Leau, Erica S.; Yu, Siyao M.; Zhang, Manlin; Kroon, Dick
Abstract: The Maldivian archipelago, in the equatorial Indian Ocean, provides a unique location to assess long‐term basin‐wide South Asian Monsoon (SAM) processes as well as its response during climatic extremes. This insight is beneficial to better understand future SAM influences on the Maldives Inner Sea physicochemical characteristics and its diverse tropical ecosystems in a warming world. This study uses samples from International Ocean Discovery Program Expedition 359, drilled within the Inner Sea drift deposits. Multiple foraminiferal species ( n  = 15) and proxies (δ 18 O, δ 13 C, and Mg/Ca) are used to assess glacial‐interglacial SAM dynamics influencing the Inner Sea conditions across Marine Isotope Stages (MIS) 1–2 and 10–13. The summer SAM is modulated by insolation and atmospheric CO2 and has a predominant impact on the northern Indian Ocean surface salinity. As with present‐day observations, a strong summer monsoon resulted in large basin‐wide δ 18 Osw (salinity) gradients during the interglacials. Moreover, at the MIS11 minimum (MIS11c), a recognized analog for the present‐day, sea surface temperatures (SSTs) were warmer than the present with a stronger summer SAM. This led to an expanded surface mixed layer and strong thermocline, resulting in a highly stratified water column and prominent oxygen minimum zone in the Inner Sea during MIS11c. SSTs in the Maldives are projected to increase at the end of this century and based on the reality that current warming (anthropogenically driven) is much faster than seen during MIS11, the Maldivian tropical coral reef and benthic shoal ecosystems will be subject to increasing stress. Key Points: The Maldivian archipelago is uniquely situated to assess, basin‐wide, northern Indian Ocean oceanographic and climatic processes An analog for the present‐day, Marine Isotope Stage 11c was warmer with a stronger summer monsoon and deeper surface mixed layer A future increase in sea temperatures with intermediate waters of lower oxygen/higher nutrient values would further stress the Maldives coral reefs